WAYS TO CONTROL AND IMPROVE PHYSICAL PERFORMANCE - Pokhachevsky, A.L.; Graf, O.V.; Petrov, A.B.; Golubeva, N.K. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to reveal the relationship between the mobility of the cervical spine and the blood circulation of the vertebral arteries, neurohumoral regulation and the physical performance of the body. Methods and structure of the study. A group of active athletes, polyathletes, track and field athletes (23 people, 17-22 years old), qualification Master of Sports, Candidate for Master of Sports, 1 sports category, was examined. The mobility of the cervical spine (CS) was assessed, an ultrasound scan of the brachiocephalic vessels (USV) was performed; if mobility disorders of the cervical spine were detected, each athlete underwent up to three sessions of individual myocorrection: acupressure, reflex, vacuum massage of the cervical spine. Heart rate (HR) indicators during the active orthostatic test and maximum exercise testing were assessed twice before and after myocorrection. Results and conclusions. In all cases of changes in the mobility of the cervical spine, USV confirmed various degrees of disturbance and asymmetry of blood circulation in the basin of the vertebral artery (VA). A decrease in the diameter of the vertebral artery corresponded to a decrease in the linear, volumetric blood flow velocity and was manifested by a low level of the total spectral power of HR, with the actual absence of fast regulatory elements. After myocorrection, the degree of restoration of blood circulation was confirmed by USV. The HR analysis revealed an increase in the total power of the spectrum and its redistribution to the high-frequency region. The results of load testing before and after myocorrection revealed significant differences in the efficiency of overcoming the load maximum and recovery. Violation of the mobility of the cervical spine, leading to a decrease and asymmetry of the blood circulation of the vertebral arteries, is manifested by depression of neurohumoral regulation and physical performance. Restoration of blood circulation after myocorrection improves the functional state and exercise tolerance.